On the Differences and Complementarities in the Fundamental Spirits of Chinese and Western Religions: A Case Study of the Concepts of Happiness in Taoism and Christianity - SUN, Yiping (Journal of Research for Christianity in China (JRCC), 2025)
Taoism, as a Chinese traditional religion, has differences in religious beliefs and fundamental spirit compare to Western Christianity. Although the Chinese Taoists are polytheists, they emphasis more on the effort made by human themselves. Start from the idea that “my destiny is control by myself, not the gods", then to rely on human’s own efforts to achieve the goal of" immortal ". The core of Christianity is the faith in God, starting from the original sin theory, emphasizing on the salvation from God. The behaviors of the human are the mani- festation of God’s will, therefore, the purpose of Christian’s life is to glory God. As a result, in order to pursuit the happiness in life, the Taoist select to maintain good health and spiritual joy, and focus on the relief of suffering and how to obtain the happiness in the secular world; in contrary, Christianity claims that the only way to regain happiness is to return to God. Based on the biblical teaching: believe, hope and love, Christians endure and obey the suffering in the secular world and pursuit the eternal happiness from the afterlife. The comparative study on the concept of happiness in this paper between Taoist - Ge Hong from Eastern Jin Dynasty and Christian theolo- gian - Augustine from the Roman Empire, demonstrates the self-consciousness of the existence and purpose of human in both religions. On the other hand, this paper strive to provide a beneficial lesson for the new cultural construction through the differences and complementarity of the fundamental spirit on the west and east relig-ions.